What Should I Eat and Why? The Environmental, Genetic, and Behavioral Determinants of Food Choice: Summary from a Pennington Scientific Symposium. Issue 8 (10th June 2020) - Qualls‐Creekmore, Emily; Marlatt, Kara L.; Aarts, Esther; Bruce‐Keller, Annadora; Church, Tim S.; Clément, Karine; Fisher, Jennifer O.; Gordon‐Larsen, Penny; Morrison, Christopher D.; Raybould, Helen E.; Ryan, Donna H.; Schauer, Philip R.; et al.
Abstract : This review details the proceedings of a Pennington Biomedical scientific symposium titled, "What Should I Eat and Why? The Environmental, Genetic, and Behavioral Determinants of Food Choice." The symposium was designed to review the literature about energy homeostasis, particularly related to food choice and feeding behaviors, from psychology to physiology. This review discusses the intrinsic determinants of food choice, including biological mechanisms (genetics), peripheral and central signals, brain correlates, and the potential role of the microbiome. This review also address the extrinsic determinants (environment) of food choice within our physical and social environments. Finally, this review reports the current treatment practices for the clinical management of eating‐induced overweight and obesity. An improved understanding of these determinants will inform best practices for the clinical treatment and prevention of obesity. Strategies paired with systemic shifts in our public health policies and changes in our "obesogenic" environment will be most effective at attenuating the obesity epidemic.